Seroprevalence of Q fever among deer livestock in UPM deer farm (PPP UPM) : preliminary study - Nur Hanis Nadhirah Yosryhan
Q fever (also known as coxiellosis) is caused by Coxiella burnetii, a widespread intracellular gram-negative bacterium associated with a zoonotic disease and reproductive disorders in animals. Although there have been extensive seroprevalence studies of C. burnetii infection in deer worldwide, data on its prevalence in Malaysia remain scarce. Thus, this preliminary study aims to assess the seroprevalence of C. burnetii infection and identify associated risk factors among deer (Cervus timorensis) livestock in Malaysia. A total of ninety-two serum blood samples were included in the study, comprising thirty-six serum samples collected in 2023 (new herd) and an additional fifty-six archived samples from 2017 (old herd), all sourced from UPM Deer Farm. The samples were screened using a commercial ID Screen® Q fever Indirect Multi-species (IDvet) kit with 99% specificity and 90% sensitivity. The result of this study has revealed an overall apparent prevalence of 14.1% (95% CI = 8.45 – 22.69) and a true prevalence of 14.8% (95% CI = 8.37 – 24.37) for Q fever among deer. The univariable analysis revealed statistically significant differences (Χ2= 8.654, p = 0.013) in seroprevalence among age groups, with adult deer exhibiting the highest apparent seroprevalence rate of 27.3% (95% CI= 15.07 – 44.22) and a true prevalence of 29.5% (95% CI= 15.81 – 48.56) followed by young adult with an apparent prevalence of 10.8% (95% CI= 4.29 24.71) and a true prevalence of 11.02% (95% CI= 3.69 26.64) and young with an apparent prevalence of 0.0% (95% CI= 0.00 14.87) and a true prevalence of 1.12% (95% CI= 1.12 15.58). Additionally, differences were observed among herds (Χ2 = 9.732, p = 0.002), with the old herd displaying an apparent prevalence rate of 23.2% (95% CI= 14.10 – 35.77) and a true prevalence of 25.0% (95% CI= 14.72 – 39.07) compared to the new herd with an apparent prevalence of 0.0% (95% CI= 0.00 9.64) and a true prevalence of 1.12% (95% CI= 1.12 9.71). However, it was revealed that there is no significant association between Q fever infection and gender (Χ2 = 2.189, p = 0.139). Multivariable logistic regression analysis further demonstrated that both age and herd were not associated (p>0.05) with seropositivity to C. burnetii. To the best of our knowledge, this study is the first documented evidence of serum antibodies towards C. burnetii among Cervus timorensis in Malaysia. Further studies are needed to isolate and characterise the strain of C. burnetii circulating among deer in Malaysia.